2011
DOI: 10.3807/josk.2011.15.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Domain Optical Coherence Tomography for Retinal Imaging with 800-nm Swept Source: Real-time Resampling in k-domain

Abstract: In this study, we demonstrated Fourier-domain/swept-source optical coherence tomography (FD/SS-OCT) at a center wavelength of 800 nm for in vivo human retinal imaging. A wavelength-swept source was constructed with a semiconductor optical amplifier, a fiber Fabry-Perot tunable filter, isolators, and a fiber coupler in a ring cavity. Our swept source produced a laser output with a tuning range of 42 nm (779 to 821 nm) and an average power of 3.9 mW. The wavelength-swept speed in this configuration with bidirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Therefore, an 800-nmcentered swept laser can be a versatile source for molecular optical spectroscopic imaging such as SOCT, near-infrared spectroscopy, diffuse optic imaging, fluorescence imaging [13] and spectrally encoded confocal microscopy [14]. While several research groups have demonstrated a swept laser near 800 nm [15][16][17][18][19][20][21], this is the first time a swept laser centered at 800 nm has been used in SOCT imaging to obtain functional information.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an 800-nmcentered swept laser can be a versatile source for molecular optical spectroscopic imaging such as SOCT, near-infrared spectroscopy, diffuse optic imaging, fluorescence imaging [13] and spectrally encoded confocal microscopy [14]. While several research groups have demonstrated a swept laser near 800 nm [15][16][17][18][19][20][21], this is the first time a swept laser centered at 800 nm has been used in SOCT imaging to obtain functional information.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the WSL with a FFP-TF had a nonlinear response in the wave-number domain, since the response of the piezoelectric transducer in the FFP-TF has a nonlinear response to a sinusoidal modulation signal. Therefore, it requires a recalibration process in the wave-number domain [2730]. …”
Section: Introductionmentioning
confidence: 99%
“…The The output of the Michelson interference is nothing but the interference pattern in the form of fringes. The interference pattern has the optical light; this optical intensity is measured by the spectrometer (Lee et al, 2011). As for image formation FFT is taken and for which the data must be evenly sampled in wavenumber space, for this resampling and interpolation blocks are followed.…”
Section: Formation Of B-scan Imagementioning
confidence: 99%
“…This data is then taken for the signal processing for the image formation (Tang et al, 2018). Figure 1 describes the working principle of Michelson Interferometer, where half-silvered beam splitter is used (Kim et al, 2018;Lee et al, 2011). Bhatia et al (2016) described the core of the OCT systems and implemented the spectral-domain OCT(SD-OCT).…”
Section: Introductionmentioning
confidence: 99%